Barriers to early presentation of self-discovered breast cancer in Singapore and Malaysia: a qualitative multicentre study. Issue 12 (21st December 2015) - Lim, Jennifer NW; Potrata, Barbara; Simonella, Leonardo; Ng, Celene WQ; Aw, Tar-Ching; Dahlui, Maznah; Hartman, Mikael; Mazlan, Rifhan; Taib, Nur Aishah
Abstract : Objective: To explore and compare barriers to early presentation of self-discovered breast cancer in Singapore and Malaysia. Design: A qualitative interview study with thematic analysis of transcripts. Participants: 67 patients with self-discovered breast symptoms were included in the analysis. Of these, 36% were of Malay ethnicity, 39% were Chinese and 25% Indian, with an average age of 58 years (range 24–82 years). The number of women diagnosed at early stages of cancer almost equalled those at advanced stages. Approximately three-quarters presented with a painless lump, one-quarter experienced a painful lump and 10% had atypical symptoms. Setting: University hospital setting in Singapore and Malaysia. Results: Patients revealed barriers to early presentation not previously reported: the poor quality of online website information about breast symptoms, financial issues and the negative influence of relatives in both countries, while perceived poor quality of care and services in state-run hospitals and misdiagnosis by healthcare professionals were reported in Malaysia. The pattern of presentation by ethnicity remained unchanged where more Malay delayed help-seeking and had more advanced cancer compared to Chinese and Indian patients. Conclusions: There are few differences in the pattern of presentation and in the reported barriers to seek medical care after symptom discovery between Singapore and Malaysia despite their differing economic status. Strategies to reduce delayed presentation are: a need to improve knowledge of disease, symptoms and causes, quality of care and services, and quality of online information; and addressing fear of diagnosis, treatment and hospitalisation, with more effort focused on the Malay ethnic group. Training is needed to avoid missed diagnoses and other factors contributing to delay among health professionals.